PELATIHAN MENGHADAPI SELEKSI KERJA - Agustinus Doedyk Setiyawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
The access toward education is not in line with the targeted job access. In the field, most of job vacancies were contradicted to the job seekers’ education background (Kompas, 15-6-2019, Pg 6). This Society Partnership Program was intended to boost trainees’ confidence to apply their targeted job. Based on the data revealed by Statistic Centre, per February 2019, 6.82 million out of 136,18 million people were jobless (Kompas, 27-7-2019). This situation led to abundant responses on one single job advertisement. From this, we can see that finding a targeted job was not easy at all. This situation, indeed, is challenging for fresh graduates who have less job experience but possess high expectation. Responding to this situation, the writers intended to equip the candidate of job seekers with special training. The subjects of the training were the sixth semester students of Business and Administration Department and English Department at State Polytechnic of Madiun. The training gave the trainees some skills. Those skills cover How to Write a Professional Application Letter, How to Write an-Online Application Letter, How to Face Psychological Test, and How to Behave and Answer Question during Job Interview. The writers hoped that the provided literacy could enhance the trainees’ motivation to find their targeted job and stay optimistic when they apply their desired job.